Structural dissection of a complex Bacteroides ovatus gene locus conferring xyloglucan metabolism in the human gut. Issue 7 (July 2016) - Hemsworth, Glyn R.; Thompson, Andrew J.; Stepper, Judith; Sobala, Łukasz F.; Coyle, Travis; Larsbrink, Johan; Spadiut, Oliver; Goddard-Borger, Ethan D.; Stubbs, Keith A.; Brumer, Harry; Davies, Gideon J.
Abstract : The human gastrointestinal tract harbours myriad bacterial species, collectively termed the microbiota, that strongly influence human health. Symbiotic members of our microbiota play a pivotal role in the digestion of complex carbohydrates that are otherwise recalcitrant to assimilation. Indeed, the intrinsic human polysaccharide-degrading enzyme repertoire is limited to various starch-based substrates; more complex polysaccharides demand microbial degradation. Select Bacteroidetes are responsible for the degradation of the ubiquitous vegetable xyloglucans (XyGs), through the concerted action of cohorts of enzymes and glycan-binding proteins encoded by specific xyloglucan utilization loci (XyGULs). Extending recent (meta)genomic, transcriptomic and biochemical analyses, significant questions remain regarding the structural biology of the molecular machinery required for XyG saccharification. Here, we reveal the three-dimensional structures of an α-xylosidase, a β-glucosidase, and two α-l -arabinofuranosidases from the Bacteroides ovatus XyGUL. Aided by bespoke ligand synthesis, our analyses highlight key adaptations in these enzymes that confer individual specificity for xyloglucan side chains and dictate concerted, stepwise disassembly of xyloglucan oligosaccharides. In harness with our recent structural characterization of the vanguard endo-xyloglucanse and cell-surface glycan-binding proteins, the present analysis provides a near-complete structural view of xyloglucan recognition and catalysis by XyGUL proteins.